IDENTITAS KOTA DAN PARIWISATA: MENAFSIR ULANG “SOLO THE SPIRIT OF JAVA” - Agus Saputro (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2022)
Identity is a distinctive identity attached to an object. Objects here can be material and non-material, with a character that the person will know and remember objects more easily. In this paper, the object studied in the city, with an identity formed through a tagline or "jargon". The city in question is Solo, with the identity to be formed as "Solo The Spirit of Java". This tagline has actually been used for a long time to brand Solo City, with various interests. In this paper, we try to explore the interpretation of the tagline, from its appearance, determination, implementation, and until now. Good interpretation of meaning, importance, and contribution to the creation of the identity of the City of Solo. The results showed that the presence of the tagline "Solo the Spirit of Java" was responded to positively by the community. The purpose of this branding is to form the image of the regional city of Subosukawonosraten in marketing for improvement, especially for the economic sector. The conclusion of this study, although it received a positive response from the public, needs to be added regarding brand strategy. Because there are data in the study, the image of the city of Solo is not too influential for tourists. Branding Strategy includes; brand positioning (the position of the brand among other similar products or brands), brand identity (what identity is raised by a product or brand), and brand personality (human attributes attached to the brand object). In addition, social capital is also an important aspect of the success of building the image of the city of Solo.